Empirical formulations for prediction of permanent set evolution of steel plates due to repeated impulsive pressure loadings induced by slamming. (15th January 2023) - Truong, Dac Dung; Huynh, Van Vu; Jang, Beom-Seon; Quach, Hoai Nam; Dang, Xuan-Phuong; Duong, Hao Dinh; Cho, Sang-Rai
Abstract: While in service, marine structures can be damaged due to repeated impact pressures induced by slamming. This paper presents empirical formulations for prediction of permanent set evolution of steel plates used in marine applications under repeated impulsive pressure arising from slamming. The applied numerical computation methodology was developed using the nonlinear finite element commercial software package ABAQUS/Explicit. The numerical analysis model was substantiated against relevant experimental data in the open literature. Subsequently, a rigorous parametric study was performed on various fully clamped plates having actual scantlings of marine structures. The effects of the key design parameters on the damage extents of the plates under repeated impact pressure loadings were determined and are presented herein. Additionally, the effects of the boundary conditions (represented by the number of stiffeners) on the permanent set evolution were addressed. Finally, through regression analysis of the parametric study results, simple empirical formulations for prediction of permanent set evolution of plates against slamming loads were derived. The accuracy and reliability of these formulations were established by comparison with existing formulations and numerical simulations. The proposed formulae are expected to be usefully employed as a quick and effective tool for the reliable prediction of marine-structural damage extents incurred from slamming loads. Highlights: A numerical model for analysis of the structural response of plates to slamming loads was developed and validated. Effects of the key design parameters on the permanent set of plates due to repeated impact pressures were investigated. Effect of boundary conditions representing the supports from surrounding stiffeners on permanent set of plates was addressed. Empirical formulae for prediction of the permanent set evolution of plates due to repeated impact pressures were proposed. The accuracy and reliability of the proposed formulations were confirmed by comparison with other methods.